A COMPARATIVE ANALYSIS OF THE RELATIONSHIP BETWEEN POVERTY AND THE ECONOMY IN IRAQI CITIES IN TRANSITION - Marwan Abdulrazak Muter (Scholar Express Journals, 2022)
The aim of this research is to look at the rates of increasing poverty in the shadow economy in Iraq, and to know if there are technical difficulties in communicating with them, as it is difficult to obtain information from the people who participated in the data collection operations. The data derived from the reality readings were used to build a realistic correlation, and the raw data was used to conduct the pilot study, where the descriptive analysis showed that poverty and the underground economy have no geographical boundaries. Although the frequency and extent of the problem varies from city to city. When compared to cities with a moderate economy, Poverty incidence rates and the economy are higher in poor cities. Poverty and the underground economy have a causal relationship, especially in low-resource and transitional cities, Where the common variables, a perception of high unemployment and corruption rates, affect poverty and the underground economy. Even when people understand the consequences when they find out, exorbitant social security systems and tax burdens have been shown to explain the high prevalence of underground economies. Most people are involved in enterprises in the form of small unlicensed activities such as production and sale of pure water and yoghurt, illegal operation of private schools, exchanging currencies in the market illegally and refraining from disclosing the real profit rate of the actual business to increase income levels. To some extent, the government may mitigate this threat by investing in longterm poverty reduction, tax policy adjustments, anti-corruption campaigns, and more jobs in the formal economy
Keywords: poverty rate; sustainable development; secret economy; subterranean economy